Decreasing corruption in the field of disaster management - Ha, Kyoo-Man (Crime, law and social change, 2023)
Corruption has always existed in the field of national disaster management. Although many case studies on (anti)corruption have been carried out, these works have not dealt sufficiently with the evidence. The present research aims to study how to shift from corruption to anti-corruption, or simply, how to decrease corruption within the system. The comparative perspective is applied as the major methodology. The "damp-ground" style is where corruption breeds, whereas the "sunshine-based" style is where disaster management ethics, structure, transparency, and regional characteristics are established, sustained, and maximized. Therefore, the personnel, system, operating principles, and other relevant factors need to evolve and change to contribute significantly to the sunshine-based model. In this regard, stakeholders should carry out their roles and responsibilities effectively to succeed in disaster impact mitigation and overall disaster management. The contribution of this work lies in providing a comprehensive viewpoint on the shift from damp-ground corruption to sunshine-based anti-corruption toward the ultimate goal of disaster mitigation.